2018
DOI: 10.1016/j.ijpam.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Combination of tacrolimus and mycophenolate mofetil in persistent proteinuria due to refractory childhood lupus nephritis

Abstract: BackgroundChildren with lupus nephritis particularly, diffuse proliferative and membranous glomerulonephritis, may necessitate potent immunosuppressive medications and occasionally combined therapy.ObjectiveTo report the beneficial effects of tacrolimus (TAC) in children with refractory lupus nephritis from a single tertiary pediatric rheumatology clinic.MethodsThis is a retrospective case series of children with refractory lupus nephritis treated with TAC after failure of aggressive immunosuppressive treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Hence, controlling proteinuria is particularly important for the treatment of lupus nephritis 8 . Many studies have found that tacrolimus has been used to treat patients with lupus nephritis and has had a good effect on controlling proteinuria 9‐11 . In addition, a published systematic review and meta‐analysis also confirmed that tacrolimus may be more effective at reducing proteinuria, having potential implications for long‐term outcome 12 .…”
Section: What Is Known and Objectivesmentioning
confidence: 94%
“…Hence, controlling proteinuria is particularly important for the treatment of lupus nephritis 8 . Many studies have found that tacrolimus has been used to treat patients with lupus nephritis and has had a good effect on controlling proteinuria 9‐11 . In addition, a published systematic review and meta‐analysis also confirmed that tacrolimus may be more effective at reducing proteinuria, having potential implications for long‐term outcome 12 .…”
Section: What Is Known and Objectivesmentioning
confidence: 94%
“…The approach of this kind of combination therapy was tested in subsequent clinical trials 28, 29, 30, 31. Meta-analysis showed that the combination therapy is more effective for inducing remission compared with IVCY, MMF, and CNIs 22, 32, 33.…”
Section: Rationale Of Combination Therapymentioning
confidence: 99%
“…Meta-analysis showed that the combination therapy is more effective for inducing remission compared with IVCY, MMF, and CNIs 22, 32, 33. Besides initial treatment, it can also help refractory or relapsing patients achieve a renal response and reduce the use of steroids 28, 29, 30, 31. Not only tacrolimus but also cyclosporine combined with MMF can induce complete remission in LN and was well tolerated 30, 31.…”
Section: Rationale Of Combination Therapymentioning
confidence: 99%